(untitled) (Journal of Economic Research & Business Administration, 2015)
Abstract. Article illustrates research results on modern approaches to the development of the integrated system of the project management at SMEs enterprises. Thus highlighting the importance of the creation operation an integrated system providing project management. This is especially important when carrying out large-scale projects or enterprises that are constantly engaged in project activities. The article highlights the following concept of a project management system which is a complex organizational and technological , methodological, technical, software and information tools aimed at supporting and improving the effi ciency of planning and project management . Summarizing the above, the author highlights the importance of international experience of integration and management systems showing the demand for expert evaluation and management of technological maturity of the enterprise. Analysis and evaluation allow drawing up a program of integration and development project management system based on the current strengths and weaknesses of the company.